Type I Gaucher disease (GDI) in three siblings: enzyme replacement treatment (ERT) required - Gucev, Z; Tasic, V; Pop Jordanova, N; Kirovski, I; Stomnaroska, O; Martinova, M; Jancevska, A; Kremensky, I; Sinigerska, I (Macedonian Academy of Sciences and Arts, 2009)
(Full text is available at http://www.manu.edu.mk/prilozi). This is a family of three children, born to healthy Macedonian parents after uneventful pregnancies and delivery. The index child was an eight-year-old girl admitted for abdominal discomfort and distension: the spleen was 14cm below the costal margin (BCM), the liver 8cm BCM. No bone pain or pathology was reported. There was mild pancytopaenia (hemoglobin 11.2 gm/L; WBC counts 4.6 x 10;3; platelets 70 x 10;3). Liver function tests, renal ultrasound, bone scan, and a chest radiograph were within normal limits. Bone marrow analysis in this child and her two brothers (11 and 6.5 years old) revealed Gaucher cells. Both brothers had only mild anaemia, but the older brother had been splenectomized prior to diagnosis of GD1. Enzyme analysis revealed low activity (2.59, 1.62, and 2.55 nmol/h/mg protein, respectively); plasma chitotriosidase levels were also elevated. Genetic testing revealed homozygosity for the N370S/N370S mutation in all three siblings. In the absence of available enzyme replacement treatment (ERT), the girl was splenectomized. Removing an important immune organ (the spleen) introduces further risk for the patients. In addition, this does not solve the bone involvement characteristic for GD. ERT should be introduced for all GD1 patients in Macedonia. Key words: Gaucher disease, N370S mutation, siblings, enzyme replacement therapy.